Theoretical assignment of the Clements bands of SO2 - Lévêque, Camille; Taïeb, Richard; Köppel, Horst (Chemical physics, 2015)
The photoabsorption spectrum of SO2 is theoretically investigated in the energy range 3.56-4.05eV (28713-32665cm−1). The lowest vibronic levels of the coupled excited electronic states (11A2/11B1) have been computed using Lanczos diagonalization of the Hamiltonian. The potential energy surfaces and the diabatization scheme used here were already successfully applied to describe the non-adiabatic dynamics of the molecule (Lévêque et al., 2013). The important vibronic states, playing a role in the experimental spectrum, have been analyzed according to their nodal pattern to propose the first theoretical assignment of the low-energy part of the spectrum. The Clements bands A-D have been assigned and exhibit contributions from numerous transitions, in the low resolution spectrum. The overlap of these transitions is shown to provide an “accidental” regularity of the Clements bands with respect to their intensities, while their regular energy spacing (∼220cm−1) results from a unique series (4,n2,1).